Protecting Malay Cultural Identity in the Land of Deli: Cultural Security Strategies in the Era of Modernization - Rifqy, Muhammad Dwi (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
The Deli Malay tribe, as one of the oldest ethnic groups in North Sumatra, faces serious challenges in maintaining its cultural identity in the midst of globalization and modernization. This research aims to identify and analyze the strategies adopted by the Deli Malay community in maintaining their cultural resilience, especially in the context of social and cultural changes that occur. Through a descriptive qualitative approach using in-depth interview methods, and participatory observation studies, this research will examine in depth the historical roots and socio-cultural dynamics of the Deli Malay community in the Land of Deli. The main focus of this research is on analyzing the impact of modernization on cultural practices, the use of the Deli Malay language, and the preservation of intangible cultural heritage such as traditional arts and customs. It is hoped that the results of this study can make a significant contribution to the development of a more effective Deli Malay cultural preservation program as well as a reference for further research on the cultural dynamics of multicultural societies in Indonesia.